Association between anaemia, iron deficiency anaemia, neglected parasitic infections and socioeconomic factors in rural children of West Malaysia - Ngui, R.; Lim, Y. A. L.; Kin, L. C.; Chuen, C. S.; Jaffar, S. (Public Library of Science, 2012)
Background: Given that micronutrient deficiency, neglected intestinal parasitic infections (IPIs) and poor socioeconomic status are closely linked, we conducted a cross-sectional study to assess the relationship between IPIs and nutritional status of children living in remote and rural areas in West Malaysia. Methods/Findings: A total of 550 children participated, comprising 520 (94.5) school children aged 7 to 12 years old, 30 (5.5) young children aged 1 to 6 years old, 254 (46.2) boys and 296 (53.8) girls. Of the 550 children, 26.2 were anaemic, 54.9 iron deficient and 16.9 had iron deficiency anaemia (IDA). The overall prevalence of helminths was 76.5 comprising Trichuris trichiura (71.5), Ascaris lumbricoides (41.6) and hookworm infection (13.5). It was observed that iron deficiency was significantly higher in girls (p = 0.032) compared to boys. Univariate analysis demonstrated that low level of mother's education (OR = 2.52; 95 CI = 1.38-4.60; p = 0.002), non working parents (OR = 2.18; 95 CI = 2.06-2.31; p = 0.013), low household income (OR = 2.02; 95 CI = 1.14-3.59; p = 0.015), T. trichiura (OR = 2.15; 95 CI = 1.21-3.81; p = 0.008) and A. lumbricoides infections (OR = 1.63; 95 CI = 1.04-2.55; p = 0.032) were significantly associated with the high prevalence of IDA. Multivariate analysis confirmed that low level of mother's education (OR = 1.48; 95 CI = 1.33-2.58; p < 0.001) was a significant predictor for IDA in these children. Conclusion: It is crucial that a comprehensive primary health care programme for these communities that includes periodic de-worming, nutrition supplement, improved household economy, education, sanitation status and personal hygiene are taken into consideration to improve the nutritional status of these children.